An experimental proof of concept of time‐reversal single‐sensor acoustic source localisation: Application to partial discharges - Hamidreza Karami; Zhaoyang Wang; Parsa Khorasani; Javad Zohrevand; Marcos Rubinstein; Farhad Rachidi (High Voltage)
Abstract In this paper, for the first time, an experimental proof of concept for utilising time reversal (TR) in the acoustic regime to localise partial discharge (PD) sources was presented using a single sensor. To achieve this, an experimental setup comprising a water tank, acoustic transducers for signal transmission and reception, and 2D scanners was developed. The performance of the proposed method was evaluated across various scenarios, encompassing different PD source locations and sensor placements, barriers obstructing the line of sight between the receiving sensor and PD sources, varying levels of noise, and different frequency bandwidths for the PD sources. The experimental results demonstrate a near‐zero localisation error in all considered examples. The achieved resolution was approximately half of the minimum wavelength. Furthermore, the acoustic TR method exhibits remarkable precision in source localisation, even when faced with obstacles such as a multi‐layered metallic cylinder and in scenarios lacking a direct line of sight between the sensor and the source. The accuracy of acoustic TR's localisation remained robust in the presence of noise, showcasing resilience at signal‐to‐noise ratio levels as low as −20 dB. Additionally, the performance of the acoustic TR method remained consistent across a broad frequency spectrum, spanning from 60 to 200 kHz.